(untitled) (Journal of Partial Differential Equations, 2020)
Sufficient conditions for existence and nonuniqueness of radially symmetric solutions to the Robin boundary problem of the form Δu + a(||x||)|u|^-p = 0 in B ⊂ R^N ∂u∂n + λu = -α on ∂B are obtained.